ANALISIS PERCEPATAN DURASI PENYELESAIAN PROYEK KONTRUKSI JALAN MENGGUNAKAN METODE TIME COST TRADE OFF DENGAN PENAMBAHAN JAM KERJA DAN JUMLAH ALAT BERAT - Moh Salman Al farisi; Zetta Rasullia Kamandang (Racic : Rab Construction Research, 2024)
Acceleration of the duration of project completion often occurs because it is influenced by several factors which cause the project to be completed before the specified time. The Time Cost Trade Off (TCTO) method is a time and cost comparison method used to shorten the implementation time of construction projects. The X arterial road project which is the case study in this research has completed 35.45% of the work with a percentage of delays that must be caught up at 5.3%. The acceleration analysis in this case study implements the TCTO method with alternative work hours (overtime) and heavy equipment on critical project work to obtain efficient results in terms of time and cost. As a result, it was found that normal labor costs and normal project duration for the remaining critical work were IDR. 802,650,747.00 with a remaining settlement duration of 89 days. Then after acceleration, we obtained an additional 4 hours of overtime work per day and additional heavy equipment with a labor cost of IDR. 278,314,091.00 which can shorten the duration by 56 days. So, based on the results of the analysis, the cost required to accelerate the X arterial road project is Rp. 1,080,964,838.39 with a completion time of 33 days.